2021
DOI: 10.1111/ahe.12747
|View full text |Cite
|
Sign up to set email alerts
|

The ultrastructure of spermatogenic cells and morphological evaluation of testicular development in the silver pomfret (Pampus argenteus)

Abstract: The silver pomfret (Pampus argenteus) is a widely distributed and economically important marine fish in the Indo‐Pacific. In this study, we acquired the second generation of wild P. argenteus by artificial breeding and further studied the testicular development and ultrastructure of spermatogenesis. The results of gonadosomatic index (GSI) showed the spawning period of this marine fish was from April to June. Besides, through morphological analysis, we found that P. argenteus had an anastomosing tubular testis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…However, only small amounts of SZ-like cells were produced in the lobules in triploid testes during the first spawning season. Compared with ultrastructural features of normal spermatogenesis in fish species (Yang et al 2021a , b ; Liu et al 2021 ; Papah et al 2013 ), triploid male yellow drum also had seven types of male germ cells including SPG, five types of SCs and SZ. However, a large number abnormal anaphase/telophase II SCs and ST varied in size and DSs were also observed in triploid testes.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, only small amounts of SZ-like cells were produced in the lobules in triploid testes during the first spawning season. Compared with ultrastructural features of normal spermatogenesis in fish species (Yang et al 2021a , b ; Liu et al 2021 ; Papah et al 2013 ), triploid male yellow drum also had seven types of male germ cells including SPG, five types of SCs and SZ. However, a large number abnormal anaphase/telophase II SCs and ST varied in size and DSs were also observed in triploid testes.…”
Section: Discussionmentioning
confidence: 94%
“…Histologically, although several scattered PNOs were observed, the ovaries of triploids were composed of a large number of CNOs. In teleosts, ultrastructural features of normal oogenesis are similar, the germ cells can be developed from oogonia into mature eggs in Bluefin Tuna ( Thunnus thynnus ) (Abascal and Medina 2005 ) and silver pomfret ( Pampus argenteus ) (Yang et al 2021a , b ). In this study, ultrastructure of germ cells showed only three types of germ cells including the OG, CNOs, and PNOs existed in triploid ovaries.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, P. argenteus and P. echinogaster exhibit remarkable morphological similarities, prompting Liu and Li (2013b) to meticulously delineate the distinguishing characteristics of the former species. Recently published studies have predominantly focused on P. argenteus, encompassing investigations into its early developmental characteristics, biological properties, and gene functionality, among other aspects (Gao et al, 2020;Al-Abdul-Elah et al, 2021;Wang et al, 2021;Yang et al, 2021a;Yang et al, 2021b). Researchers have employed diverse molecular markers to investigate disparities among Pampus species.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, most of the body's energy is used for reproductive processes. Under artificial breeding conditions, we discovered instances of ovarian atresia and asynchronous sperm development in some silver pomfret specimens [33, 34]. Additionally, due to generations of breeding, the gonad development of silver pomfret in artificial culture has been accelerated.…”
Section: Introductionmentioning
confidence: 99%